Bacteria divert resources from growth for magellanic penguin chicks - Potti Sánchez, Jaime (2002)
The influence of bacteria on the growth of their wild avian hosts is unknown. We tested experimentally whether administration of a wide-spectrum antibiotic (cephalosporine) during early development of magellanic penguin (Spheniscus magellanicus) chicks had any effect on their growth rates in the wild. Chicks that were injected in two occasions with cephalosporine grew faster than control untreated chicks. The positive effect of medication on nestling growth disappeared after the treatment ceased, did not alter haematological indices indicative of health status, had no influence on chick survival until near independence and was related to a changed bacterial composition of the faecal microbiota of treated chicks when compared with that from control chicks. These results were similar to those obtained for poultry with antimicrobials promoting growth and chick nutrient assimilation rates. Gram-positive bacilli in the diphtheroid genus Corynebacterium are likely candidates to cause decreased growth rates in magellanic penguin chicks.